2022
DOI: 10.1002/fsn3.3054
|View full text |Cite
|
Sign up to set email alerts
|

Improving the adsorption characteristics and antioxidant activity of oat bran by superfine grinding

Abstract: Oat bran (OB) is a by‐product of oat, which is rich in β‐glucan. As a new food processing technology, ultrafine powder can improve the surface properties of samples. OB with different grinding times was prepared, and its functional components, physical properties, adsorption properties, and antioxidant properties were evaluated. Results showed that with increased grinding times, the average particle size of OB decreased significantly (p < .05). And the water‐holding capacity, swelling capacity, and water solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…A positive association exists between elevated serum cholesterol levels and increased susceptibility to ischemic heart disease [ 90 ]. Numerous studies have demonstrated that foods rich in soluble dietary fiber can effectively reduce blood lipid levels by inhibiting the absorption of cholesterol and bile acids in the intestines [ 88 ].…”
Section: Biological Function Of Fermented Oatsmentioning
confidence: 99%
“…A positive association exists between elevated serum cholesterol levels and increased susceptibility to ischemic heart disease [ 90 ]. Numerous studies have demonstrated that foods rich in soluble dietary fiber can effectively reduce blood lipid levels by inhibiting the absorption of cholesterol and bile acids in the intestines [ 88 ].…”
Section: Biological Function Of Fermented Oatsmentioning
confidence: 99%
“…These findings underscore the importance of a holistic dietary approach. Human studies further emphasize the relevance of fermented oats in inducing anti-obesity and anti-cholesterol effects on lipid metabolism [ 188 , 189 ].…”
Section: Ingredients For Functional Foods and Beverages With Promisin...mentioning
confidence: 99%
“…The increased risk of ischemic heart disease is correlated with elevated serum cholesterol levels [ 84 ]. Studies show that foods with soluble dietary fiber lower blood lipids by reducing the intestinal absorption of cholesterol and bile acids [ 41 ].…”
Section: Health Benefitsmentioning
confidence: 99%